2021
DOI: 10.1128/msphere.00564-21
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Neurospora crassa Sulfur Starvation Response Are Revealed by Transcriptional Profiling and DNA Affinity Purification Sequencing

Abstract: Identification of nutrients present in the environment is a challenge common to all organisms. Sulfur is an important nutrient source found in proteins, lipids, and electron carriers that are required for the survival of filamentous fungi such as Neurospora crassa .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Previous studies on N. crassa , Penicillium expansum , and A. nidulans have shown that the deletion of cys-3 / metR significantly reduces the transcript levels of sulfur assimilation genes and their enzyme activities, aligning with the observations in this study ( 21 , 37 , 38 ). In addition, in N. crassa , random sequence oligonucleotides and DAP-seq analysis revealed CYS3 binding motifs as 5′-ATBRCGCCATC-3′ and 5′- ATGGCGCCAT -3′ ( 25 , 41 ), which exhibit high similarity to the motif analysis results in this study. Overall, these findings demonstrate that Fgbzip007 is a functional ortholog of the CYS3/METR and, like typical bZIP proteins, plays a significant role in a wide range of mechanisms including nutrient utilization and stress response.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies on N. crassa , Penicillium expansum , and A. nidulans have shown that the deletion of cys-3 / metR significantly reduces the transcript levels of sulfur assimilation genes and their enzyme activities, aligning with the observations in this study ( 21 , 37 , 38 ). In addition, in N. crassa , random sequence oligonucleotides and DAP-seq analysis revealed CYS3 binding motifs as 5′-ATBRCGCCATC-3′ and 5′- ATGGCGCCAT -3′ ( 25 , 41 ), which exhibit high similarity to the motif analysis results in this study. Overall, these findings demonstrate that Fgbzip007 is a functional ortholog of the CYS3/METR and, like typical bZIP proteins, plays a significant role in a wide range of mechanisms including nutrient utilization and stress response.…”
Section: Discussionsupporting
confidence: 80%
“…Our results showing that Fgbzip007 interacts with FGSG_08463 and FGSG_08528 involved in sulfur metabolism led us to identify the genes encoding enzymes involved in the sulfur assimilation pathway in F. graminearum . Based on previous reports that identified genes for the sulfur assimilation pathway in N. crassa and A. nidulans ( 25 , 26 ), we identified seven genes, including FGSG_08463 and FGSG_08528, in this study that encode sulfate permease, sulfate adenylyltransferase, adenylyl-sulfate kinase, phosphoadenosine phosphosulfate (PAPS) reductase, and sulfite reductase using BLASTp analysis: CYS13, CYS14, CYS11, ADSK1, CYS5, CYS2 , and CYS4 ( Table 1 ). When we analyzed the transcript levels of these genes under sulfur-deprived conditions, all genes were upregulated in the wild-type strain 2 h after being transferred to a sulfur-deficient condition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 86 , 88 Two genes viz., cys-13 (permease I) and cys14 (permease II) which encode the N. crassa sulfate transporters are of high affinity in nature. 87 , 89 Sulfur sources, like sulfate or methionine, regulate both the genes at the transcriptional level. Under sulfur starvation, both genes have been shown to be highly expressed.…”
Section: Sulfate Permeases In Fungimentioning
confidence: 99%
“…retain the ability to bind DNA and act as the main (and possibly the sole) regulators controlling the pathway 33,34 . In all these species Met4 is absolutely required for methionine biosynthesis, and its disruption results in methionine auxotrophy 25,[32][33][34] . Nothing is known about sulphur assimilation and cysteine/methionine biosynthesis in C. parapsilosis.…”
Section: Introductionmentioning
confidence: 99%